Numerical modeling of surface acoustic wave for silica tapered fiber - Lee H.J.; Abdullah F.; Ismail A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Acoustic surface wave devices; Acoustic waves; Acoustics; Brillouin scattering; Chemical bonds; Fibers; Finite element method; Molecular orbitals; Numerical methods; Numerical models; Quantum chemistry; Silica; Stimulated Brillouin scattering; Wave functions; Co-existence; Fundamental modes; Overlap integrals; Propagation constant; Reliable models; Silica fibers; Surface acoustic waves; Tapered fiber; Fiber amplifiers